«Du fungerer mer som et menneske.» Norske revmatikeres erfaringer med helse og dagligliv i Spania. - Gregersen, Anne-Grethe; Helgesen, Ann Karin (Nordisk Tidsskrift for Helseforskning, 2015)
The objective of this study is to illuminate the experience of Norwegian rheumatics illness during long-term residency in Spain. The method chosen is qualitative with a phenomenological approach. Twelve rheumatics comprise the sample group, eight women and four men, ages from 45 to 70. Data collection was performed by qualitative research interview. The data is analyzed using condensation, followed by a thematic approach, inspired by Giorgis phenomenological method. The essence of the Norwegian rheumatics experience is that they recovered control over everyday life. They experienced pain relief, reduced medication and increased personal activity. The study indicates that long-term stay in Spain can promote health for people suffering weather-sensitive rheumatism.